F4H5 alleviates increased outflow resistance induced by emulsified silicone oil in vitro - Muuß, Marcel; Karaivanova, Margarita; Skrzypczyk, Lea; Wohlfart, Sabrina; Herth, Jonathan; Uhl, Philipp; Auffarth, Gerd U.; Hammer, Maximilian (Investigative ophthalmology & visual science, 2025)
The purpose of this study was to investigate the effect of emulsified silicone oil on trabecular outflow resistance using an in vitro perfusion model of human and porcine anterior segments. F4H5, an approved washout for emulsified silicone oil in the posterior segment, was evaluated as a potential rescue treatment. Seventeen porcine and 15 human anterior segments were dissected and clamped into an in vitro perfusion model. The intraocular pressure (IOP) was recorded continuously and evaluated before and after the injection of emulsified silicone oil, followed by treatment with F4H5 in the intervention group. Control eyes received injections of balanced salt solution (BSS). In human eyes, the injection of emulsified silicone oil significantly increased IOP from 7.8 ± 1.3 millimeters of mercury (mm Hg) to 15.8 ± 3.5 mm Hg (increase of 8.0 ± 2.3 mm Hg, P = 0.02, mean time to stabilized higher pressure = 8.6 hours). Subsequent treatment with F4H5 reverted the IOP back to near baseline values (10.8 ± 2.2 mm Hg, P = 0.06 compared to baseline, mean time to stabilized lower pressure = 6.9 hours). Porcine eyes demonstrated comparable trends, with a significant IOP increase from 14.5 ± 1.2 mm Hg to 17.7 ± 1.6 mm Hg after silicone oil injection (increase of 3.2 ± 0.9 mm Hg, P = 0.01) and a subsequent significant drop in IOP to 12.4 ± 1.0 mm Hg after the injection of F4H5 (decrease of 5.3 ± 1.1 mm Hg, P < 0.01). Emulsified silicone oil leads to blockage of the outflow pathways and an increased IOP in an in vitro human and porcine anterior segment perfusion model. With F4H5, a clinically relevant reversal of this increased outflow resistance was achieved and should be further evaluated.